Transforming Philippine Agriculture : During COVID-19 and Beyond - World Bank (World Bank, Washington, DC, 2020)
Like other rapidly growing and urbanizing middle-income countries, the Philippines is experiencing a structural transformation of its economy. Structural transformation has progressed slowly in the Philippines, however, indicating that Philippine agriculture is not performing to its potential and therefore not fully delivering to the national (and rural) economy. The new strategic vision for the agricultural sector is a food-secure and resilient Philippines with prosperous farmers and fisherfolk. This new thinking for accelerating agricultural transformation recognizes both the limitations of and potential for the agricultural sector in the COVID-19 (Coronavirus) context. This report outlines policy and investment options to promote the development of a more diversified agriculture and food system that will enhance the welfare of the rural population and improve food security for the population at large. This report considers the major programs of the department of agriculture (DA) and trends in spending patterns over the last few years, although it is not a comprehensive review of agricultural policies and public expenditures, owing to a lack of data. This report comprises five chapters. Chapter one is introduction. Chapter two provides an overview of the agricultural sector, highlighting important trends over time, the current situation, and challenges. Chapter three reviews programs of the DA and attached agencies, including the major banner programs. Chapter four discusses policy reforms, institutional changes, and investments that have produced transformational change in the agri-food sector in other countries and explores how the Philippines can use lessons from these experiences. Chapter five presents recommendations for future policy directions.